Connecting communities enhancing the cultural impression and the somatic experience in Talim Island, Binangonan using Barangay Janosa as its center - Buenafe, Cherrie A. (College of Architecture, University of the Philippines Diliman, 2017)
The language we speak, the art, literature, and the heritage we are proud of, our food, our festivals, and our customs and traditions together form our culture. It sets our identity as a group, as a community, and as a nation. Culture unites and gives people a sense of security, but as urban advancement grows, people's attention shifts from old traditions to new technologies. People tend to work on what they believe are more important in order to live, neglecting the preservation of culture, which in turn, results to the disintegration of the community's identity. Talim Island who is supposedly protected from the influences of urbanization due to its location is showing evidences of urban growth on the Binangonan area, and the strong cultural value of the community slowly disintegrates; losing its identity as a community. The study aims to reestablish the identity of the island as one community and unify the residents from the different barangays, "connecting communities", by forming a convergence zone, an area that will give reasons for the residents from the diffent barangays to communicate and interact with one another, taking their interest by setting various activities that will highlight the culture of the whole Talim Island. With the use of Barangay Janosa as center of the landscape development for potential somatic activities intended for self-growth while influencing the communal - interest of the individuals, through learning the culture of Talim Island by fully comprehending the identity of the community using firsthand experiences.